2009
DOI: 10.3758/app.71.5.1059
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms of priming of pop-out: Stored representations or feature-gain modulations?

Abstract: Previous research has shown that repetition of a task-relevant attention-capturing feature facilitates popout search. This priming of pop-out effect is due to some residual memory from recent trials. We explore two possible mechanisms of priming of pop-out: a top-down attentional benefit from a memory of the previous target representation that is stored in visual short-term memory (VSTM) and a bottom-up change of attentional gains from perceptual features of the previously attended target. We manipulated parti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

9
50
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 40 publications
(59 citation statements)
references
References 30 publications
9
50
0
Order By: Relevance
“…Experiment 1A replicated the findings from Lee et al (2009): The magnitude of PoP was not influenced by a concurrent non-spatial VWM task. More importantly, Experiment 1B demonstrated that the magnitude of PoP decreased when spatial VWM was loaded.…”
Section: Discussionsupporting
confidence: 77%
See 4 more Smart Citations
“…Experiment 1A replicated the findings from Lee et al (2009): The magnitude of PoP was not influenced by a concurrent non-spatial VWM task. More importantly, Experiment 1B demonstrated that the magnitude of PoP decreased when spatial VWM was loaded.…”
Section: Discussionsupporting
confidence: 77%
“…Experiment 1 was designed as a replication and extension of Lee et al's (2009) study. In Experiment 1A, we loaded nonspatial VWM while participants performed a color-oddball task in the periphery, and in Experiment 1B, we simply changed the load to a spatial VWM load.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations